Kajian Eksperimen Kemampuan Penyerapan Energi Pada Struktur Sarang Lebah Yang Diuji Secara Statis - Lubis, Sudirman; Siregar, Ahmad Marabdi; Siregar, C A; Siregar, Irpansyah (Fakultas Teknik UMSU, 2021)
The honeycomb structure is a natural or man-made structure (material) that has a honeycomb geometry, which is aimed at lightweight construction material companies, also getting a quality level from the material selection. The purpose of this study was to analyze the energy absorption ability of the statistical pressure tester. Energy absorption is a method of how an object attenuates due to external pressure. The energy absorption test was carried out by means of a statistical press test, the test object made from aluminum plates in the form of a honeycomb structure with different hexagonal size variations. This section will compare the results of the stress-strain and energy absorption data on each tested specimen to see which one is more efficient among the three specimens with different hexagonal sizes. The final result of this tester will use a graph of vertical stress - strain and energy absorption capability by horizontal and vertical testing. Therefore the results of the greatest energy absorption are in the horizontal test position with a hexagonal size of 2 mm, and the energy placement is in a vertical test position with a hexagonal size of 6 mm.